Ontological Background of the Literature at the Sample of the Evolution of Homo Muslimus -II-: Applications on the Holist Heqmatic Grounds - Açıkgöz, Hacı (My University, 2020)
In this paper, I shall in general offer a critical account of a topic which is about ‘historic emergence of language, thought and religion at the three-sided evolution of homo Muslimus’ at the factual, conceptual and historical levels within the context of the trio of ‘agent’, ‘action’ and ‘agency’. The paper obtained by means a holist heqmatic inquiry, which is applied into the topic in the frame of the Books of Universe and the Qur’an. Thus we offer a historical horizon and momentum about the intellectual onto-epistemic journey of man called by us as homo skeptikus who is divinely expected to be a ‘homo Muslimus’. Our investigation covers two interconnectedly succeeding separated articles which are about the same topic and title. This current article is the second part presented here includes ‘applications on holist heqmatic ground’ of the research topic.

Bu makalede olgusal, kavramsal ve tarihi zeminlerde ‘eyleyen’, ‘eylem’, ‘eyleyenlik’ bağlamında ‘homo Muslimus’un üç taraflı evriminde dil, düşünce ve dinin tarihsel ortaya çıkışı’ konusuna dair eleştirel bir irdeleme yapılarak evren ve Kur’an kitaplarının bizce okunması çerçevesinde yeni bir bakış açısı ve yorum öneresinde bulunulmuştur. Böylece ilahi yaratılış amacı ve donanımı gereği homo Muslimusluğa evrilmesi beklenilen ve bizce üst yapısal donanımından dolayı ‘homo skeptikus’ adı verilen insanın onto-epistemolojik yolculuğuna dair tarihi bir ufuk ve hareket noktası önerisinde bulunacağız. Araştırmamız aynı konuya dair birbirini ardılı aynı isimli iki müstakil makaleden oluşmaktadır. Burada sunulan makalemiz konunun ‘tümcü hikmeti zemindeki uygulamaları’ içeren ikinci makaledir’.
Homo Muslimus’un Evrimi Örneğinde Literatürün Ontolojik Arkaplanı -II: Tümcü Hikmeti Zemindeki Uygulamalar